‘It’s not just the drugs that are difficult to quit’: women’s drug dealing as a source of empowerment and its implications for crime persistence - Grundetjern, Heidi (The British journal of criminology, 2019)
Research comparing crime desisters with persistent offenders has tended to find persisters to be a marginalized group who, for personal, interactional and/or structural reasons, are unable to break free from crime. On the basis of in-depth interviews with a group of empowered women drug dealers in Norway, this article suggests that the processes of psychological empowerment emerging within some individuals’ criminal success are an under-investigated aspect of crime persistence. We describe how these processes are gendered in important ways. Empowerment was prominently linked to what the women recognized as their hard-earned place at the table as successful drug dealers, including their skill in navigating a gendered field in which the presumptive female subject is marginalized and sexualized. Our findings demonstrate that success in the drug market is fuelled by and fuels women’s empowerment, and also that such empowerment can be a significant deterrent for attempts at and the desire to desist. Our findings have import for research on the rewards of crime, for scholarship on gender and crime as well as for scholars of desistance.